Facemask Wearing Among Chinese International Students From Hong Kong Studying in United Kingdom Universities During COVID-19: A Mixed Method Study - Lai, Agnes Yuen-kwan; Sit, Shirley Man-man; Lai, Theresa Tze-kwan; Wang, Man-ping; Kong, Cecilia Hoi-mei; Cheuk, Jessica Yuet-ying; Feng, Yibin; Ip, Mary Sau-man; Lam, Tai-hing (Frontiers in Psychiatry, 2021)
Background: The mental health of international students studying abroad has been neglected during the COVID-19 pandemic. Objective: This mixed-method study examined perceived public attitudes, personal beliefs, practice and stress toward facemask wearing as a preventive measure against COVID-19 among international university students from Hong Kong studying in the United Kingdom (UK) in the early stage (January – March 2020) of the pandemic. Methods: Our study included 2 parts: (i) an exponential, non-discriminative snowball sampling strategy was used to recruit 91 Chinese students studying in the UK to complete an online questionnaire survey, and (ii) online Zoom focus group interviews were conducted with 16 students who completed the online survey to gain an in-depth understanding of their experiences and coping methods during the pandemic. Results: Of the 91 students, 92.3% reported the UK public did not view facemask wearing as a preventive measure. 98.9% believed facemask wearing was an effective preventive measure, but 56% wore facemasks more than half of the time when out in public. 50.5% had internal conflicts of stress both when wearing and not wearing facemasks, which was more common in females than males [(62.5% versus 31.5%, P=0.004, Relative Risk (RR): 1.99 (1.17, 3.38)]. 61.5% reported public prejudiced attitudes against facemask wearing, also more common in females than males (71.4% versus 45.7%, P=0.02, RR: 1.56 (1.05, 2.32). Qualitative findings showed conflict between personal beliefs and social norms, stress about wearing facemasks as a preventive measure and experiences with prejudice. Peer and family support helped students face such difficulties. Positive thinking and adaptability were effective methods of stress management. Qualitative findings corroborated the quantitative results. Conclusions: Prejudiced attitudes and behaviours from others, and differences in public attitudes toward facemask wearing has resulted in high levels of stress among students. Clear and accurate public health messaging regarding facemask wearing is needed to change public attitudes and mitigate prejudice. Owing to the ongoing pandemic and rising xenophobia, specifically Sinophobia, academic institutions and public health professionals should take initiative in reaching out to address the urgent needs of international students, and provide proactive support for stress management and enhancing mental wellbeing.